Means to Prevent Complications in Patients with Cold Trauma - Sazonova, Taisiia M.; Protsenko, O. S.; Shapoval, Olena V. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 158